SINTESIS NANOSILIKA DARI ABU KETEL INDUSTRI GULA DENGAN METODE ULTRASONIKASI DAN PENAMBAHAN SURFAKTAN - Andes Ismayana, Akhiruddin Maddu, Illah Saillah, Ersyad Mafquh, Nastiti Siswi Indrasti (Jurnal Teknologi Industri Pertanian, 2017)
Boiler ash from sugar industry contains silica compounds which could be synthesized into nanosilica by ultrasonication method. The addition of surfactants in this synthesis method can affect the characteristics of nanosilica. This study aims to synthesize nanosilica with ultrasonication method and determine the effect of surfactants on characteristics of nanosilica generated. This research was divided into three stages: (1) boiler ash preparation to furnace ash, (2) silica extraction from furnace ash, and (3) synthesis of nanosilica using ultrasonication method with surfactant addition: PEG 6000 1:5, CMC 2.5% (b/b), CMC 5% (b/b), CMC 10% (b/b), and Tween 80 3% (b/v). Silica content in boiler ash and furnace ash was 49.69% and 78.75%, respectively. The nanosilics produced using the ultrasonication method had the uniform size (PDI) of 0.638, and with the addition of surfactant might increase the uniformity of the particle (PDI) to 0.045 and 0.047 on the usage of CMC 5 and 2.5%. The addition of surfactant also increased the crystallinity degree from 76.96% at no surfactant to 84.04% with 10% CMC surfactant added. The crystalline size of the silica nanoparticles also became smaller with the addition of 10% CMC of 37.69 nm from 41.40 nm crystal size without the addition of surfactant. The addition of an enlarged CMC concentration would increase the degree of crystallinity and decrease the crystal size of the nanosilica particles.Keywords : boiler ash, nanosilica, ultrasonication, surfactant, degree of crystallinity